GE_GERICHTE C/15498/2013 vom 10. Dezember 2013 - GE Cour de justice (2013)
MAINLEVÉE PROVISOIRE; TITRE DE MAINLEVÉE; CRAINTE FONDÉE; COMPENSATIO; ANNULABILITÉ; RECONNAISSANCE DE DETTE | LP.82; CO.17; CO.30.2; CO.31.1